Phytotherapy In Primary Health Care: An Integrative Literature Review - de Assis, Ana Beatriz Carneiro; Pinheiro, Maria das Dores Viana; Santos, Charles Nonato da Cunha; do Carmo, Márcia Naildes da Costa Lima; Santiago, Paulo Giovanni Lima; Cruz, Juliana de Sousa Oliveira Ximenes; da Luz, Mauricio Pereira; Nunes, Jossiony Helly de Freitas; Garcez, Michel Alexander Araújo; Pereira, Raquel Conceição Guajajara; de Castro, Felisangela dos Santos; e Silva, Felipe Santana (Seven Editora, 2023)
Objective: The present study aimed to analyze the use of phytotherapy and medicinal plants in Primary Health Care. Methodology: This is an exploratory and descriptive qualitative research carried out through an integrative literature review. The study used three databases, from 2017 to 2022, using 21 publications. Results and Discourse: Older articles were used due to the wealth of information. The use of medicinal plants results from a vast knowledge that for centuries have been used by different ethnic groups resulting in what we now know as traditional medicine, which was recognized by the World Health Organization. Final Considerations: It was possible to identify in the study that there is a great shortage in terms of studies and publications regarding phytotherapy, even though our country is the largest plant biodiversity in the world. With training, information and research incentives, Primary Health Care has great potential to change this reality. DOI: https://doi.org/10.56238/colleinternhealthscienv1-092